Worker life tables, survivorship, and longevity in colonies of Bombus (Fervidobombus) atratus (Hymenoptera: Apidae) - da Silva-Matos, Eunice Vieira (Universidad de Costa Rica, 2000)
Survivorship curves and longevity of workers were studied in two queenright and two queenless colonies of Bombus (Fervidobombus) atratus. Survivorship curves for workers of all colonies were, in general, convex, indicating an increasing mortality rate with increasing age. The mean longevity for the workers from queenright colonies, 24.3 days and 17.6 days, was not significantly different from !hat in queenless colonies, 21.2 days and 20.2 days. In all colonies workers started foraging activities when aged 0-5 days, and the potential forager rates rose progressively with increasing age. Mortality rates within each age interval were significantly correlated with the foraging worker rates in all colonies. Only in two of the colonies (one queenright and one queenless) longevity was significantly correJated with worker size. The duration of brood development period seems lo be one of the most important factors influencing adult worker Jongevity in bumble bee species.